Uji Sensitifitas Sari Buah Pare (Momordica charantia L) pada Bakteri Edwardsiella tarda dengan Metode Difusi Kertas Cakram Secara In Vitro [Sensitivity Test Of Fruit Bitter Melon Juice (Momordica charantia L) On Bacteria Edwardsiella tarda With Paper Disc Diffusion Method In Vitro] - Sudarno Sudarno; Selvi Lely Rosanti; Sri Subekti (Faculty of Fisheries and Marine Universitas Airlangga, 2012)
Abstract One of the problems encountered in fish farming is the disease attack. The attack of disease that was caused by bacteria is a problem that often occur in aquaculture. Traditional medicine is more readily accepted by communities because is cheap and easily available, have been quite familiar with the community. There were various kind of traditional medicine and has been widely studied chemically content and usefulness. Therefore there were still many plants unknown levels of toxicity, therefore need further study. Bacteria E. tarda spread in some countries such as Europe, Japan, Taiwan, Thailand, United States, Singapore, and Malaysia. While in Indonesia E. tarda were found in Java, Sumatra, and Borneo. The aim of the research is to know the capabilities of the inhibition zone of fruit bitter melon power against the bacteria E. tarda in vitro and knowing whether fruit bitter melon effective in inhibiting the growth of the bacteria E. tarda with gold standard comparator antibiotics Tetracycline. The research was conducted on February 2011 in Bacteriology and Microbiology, laboratory in Fish Quarantine Juanda Sidoarjo district of East Java. The method used in this research is descriptive method that was done in vitro by using sensitivity test of diffusion method with the determination of inhibition zone by comparing with antibiotic inhibition zones. The results showed that bitter melon juice has a bacterial growth inhibition against E. tarda, although when was compared with gold standard antibiotic tetracycline shared considered less sensitive. Observations showed clear zone of bitter melon fruit juice shared with a diameter of 13.3mm, was compared with standard antibiotic tetracycline can inhibit with a minimum diameter of 15mm. Sensitivity test of bitter melon fruit juice will be classified as not susceptible to the bacteria therefore is able to inhibit E. tarda..